Successful Postnatal Cardiopulmonary Resuscitation Due to Defibrillation - Lukas Peter Mileder; Nicholas Mark Morris; Stefan Kurath-Koller; Jasmin Pansy; Gerhard Pichler; Mirjam Pocivalnik; Bernhard Schwaberger; Ante Burmas; Berndt Urlesberger (Children, 2021)
An asphyxiated term neonate required postnatal resuscitation. After six minutes of cardio-pulmonary resuscitation (CPR) and two doses of epinephrine, spontaneous circulation returned, but was shortly followed by ventricular fibrillation. CPR and administration of magnesium, calcium gluconate, and sodium bicarbonate did not improve the neonate’s condition. A counter shock of five Joule was delivered and the cardiac rhythm immediately converted to sinus rhythm. The neonate was transferred to the neonatal intensive care unit and received post-resuscitation care. Due to prolonged QTc and subsequently suspected long-QT syndrome propranolol treatment was initiated. The neonate was discharged home on day 14 without neurological sequelae.